Bibliometric and Systematic Review of Islamic Education Learning Quality: Trends, Gaps, and Future Directions - Wanada Siti Salsabilah; Maisah Maisah; Roudoh Roudoh (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to identify trends and developments in research on the quality of Islamic Religious Education (IRE) learning in the period 2015–2025 using a bibliometric approach and systematic review and to reveal the main factors that contribute to improving the quality of Islamic religious education learning. Methodology: This study used bibliometric analysis and systematic review. Data were obtained from the Scopus database with related keywords. The analysis was performed using VOSviewer software for network visualization and research trends. Articles were selected based on the inclusion criteria of 2015–2025 and in English. Quantitative and qualitative approaches were used in data analysis. Main Findings: This study found that the research trend on the quality of Islamic Religious Education (IRE) learning increased significantly from 2017 to 2020, decreased in 2021, and then increased again from 2022 to 2025. The main contributing factors include teacher competence, quality management, madrasah leadership, and the integration of technology. The Total Quality Management (TQM) approach and innovation in learning methods have proven effective in improving the quality of Islamic Religious Education (IRE) learning. Novelty/Originality of this study: This study provides new insights into the global trends of Islamic Religious Education learning quality research through bibliometric analysis and systematic review. This study identifies research gaps, key factors for improving learning quality, and the integration of technology and Total Quality Management (TQM) in IRE, which have not been comprehensively discussed in previous studies.